THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND PSYCHOLOGICAL CAPITAL ON JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT AMONG HEALTH ASSISTANTS AND NURSES IN SAUDI ARABIAN HOSPITALS - Faris Falih Alharbi, Fayez Fahs Awaid Aldhafeeri, Khalid Malouh S Aldhafeeri, Sami Ageel Shelan Al dhafeeri, Haif Ayed Hamlan Aldhafeeri, Romiah Kheleaif AL Dhfeeri Dhuha Hassan Hnatan Alanzi, (Chelonian Research Foundation, 2022)
Maintaining a satisfied and committed workforce is crucial for healthcare organizations to provide high-quality patient care and achieve organizational goals. This study aims to examine the influence of transformational leadership and psychological capital on job satisfaction and organizational commitment among health assistants and nurses working in hospitals across Saudi Arabia. A cross-sectional survey design was employed, and data were collected from a sample of 500 health assistants and nurses using validated questionnaires. The findings revealed that both transformational leadership and psychological capital had significant positive effects on job satisfaction and organizational commitment. Furthermore, psychological capital partially mediated the relationship between transformational leadership and the two outcome variables. The results highlight the importance of fostering transformational leadership practices and developing psychological capital among healthcare workers to enhance their job satisfaction and organizational commitment. The implications of these findings for healthcare management and future research directions are discussed. Keywords: transformational leadership, psychological capital, job satisfaction, organizational commitment, health assistants, nurses, Saudi Arabia